The Role Of Digital Simulation in Enhancing Conceptual Understanding Of Physics Among University Students - Luis A. Herrera; Rosa M. Rodríguez; Carlos R. Lopez (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
This study examines the role of digital simulations in improving university students' understanding of complex physics concepts. Utilizing an experimental design, the research assessed students' conceptual grasp before and after the use of digital simulations in instructional sessions. Results indicated a significant improvement in students' understanding and retention of physics concepts, particularly in areas such as electromagnetism and quantum mechanics. The findings support digital simulation as an effective tool for enhancing conceptual learning in science education.